2005
DOI: 10.1016/j.lungcan.2005.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of survivin-2B and survivin-ΔEx3 is inversely associated with disease relapse and patient survival in non-small-cell lung cancer (NSCLC)

Abstract: SummaryAlthough it was observed that inhibition of the antiapoptotic protein survivin expression in lung cancer cells induces apoptosis, the expression and role of survivin variants (survivin-2B and survivinΔEx3) in lung cancer have not yet been characterized. We analyzed 24 non-small-cell lung cancer (NSCLC) samples by semi-quantitative RT-PCR. Surprisingly, our results revealed that high-level expression of survivin-2B is significantly associated with the patient category of "no relapse and alive" (p-value <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 12 publications
6
50
0
2
Order By: Relevance
“…On the other hand, previous immunohistochemical studies revealed the nuclear expression of survivin proteins also to be associated with tumour cell proliferation and a poor prognosis in cancer patients, as was also shown in the present study, while the cytoplasmic expression of survivin proteins was not (Martinez et al, 2004;Huang et al, 2005;Ling et al, 2005;Shinohara et al, 2005;Taubert et al, 2005). These studies were performed using antibodies against pan-survivin, which cannot distinguish wildtype survivin from other spliced variants.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…On the other hand, previous immunohistochemical studies revealed the nuclear expression of survivin proteins also to be associated with tumour cell proliferation and a poor prognosis in cancer patients, as was also shown in the present study, while the cytoplasmic expression of survivin proteins was not (Martinez et al, 2004;Huang et al, 2005;Ling et al, 2005;Shinohara et al, 2005;Taubert et al, 2005). These studies were performed using antibodies against pan-survivin, which cannot distinguish wildtype survivin from other spliced variants.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, previous clinical studies also revealed the survivindeltaEx3 expression to be associated with a high proliferation rate (Takashima et al, 2005). Recent studies have revealed that the survivin-deltaEx3 overexpression is a significant poor prognostic factor in cancer patients, including NSCLCs (Ling et al, 2005;Taubert et al, 2005). Furthermore, the present study found the survivin-deltaEx3 gene expression to be significantly higher in advanced-stage NSCLCs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Survivin is a protein which travels frequently between the cytoplasm and nuclear locations and it requires an active temperature-sensitive import mechanism. Growing evidence has indicated that there is mitochondrial localization of survivin in cancer cells, 28,29) and the intracellular transport of survivin is very important for the antiapoptosis effects of the protein. 29,30) Taking all these together, the overexpression of Pgp may mediate intracellular protein transport, which might facilitate the transport of survivin from one location to another and induce hyperfunctioning of the protein not only in anti-apoptosis but also in chemoresistance.…”
Section: Effect Of Survivin On Pgp Functionmentioning
confidence: 99%
“…Spliced variants identified to date include Survivin 2 (Caldas et al, 2005;Mahotka et al, 2002) , 2B, Ex3 (Ling et al, 2005;Mahotka et al, 1999;Mahotka et al, 2002;Song & Wu, 2005) and 3B (Badran et al, 2004), and some of these variants have been evaluated for their anti-or pro-apoptotic function and ability to interact with wild-type Survivin and other chromosomal passenger proteins (CPC) in some model systems. More recently, several new Survivin splice variants were found in the expressed sequence tag (est) database or described based on RT-PCR using RNA from Molt-4 cells (Li & Ling, 2006;Mola et al, 2007), however the biological functions of these new variants are not known.…”
Section: Survivin Splice Variantsmentioning
confidence: 99%